Practical leadership and management in nursing - Sullivan, Eleanor J.; Garland, Gayle; Sullivan, Eleanor J. (Harlow, England ; New York : Pearson, 2010)
Team work, management, & leadership skills are an important part of being a nurse. This is the perfect book to help you on your way to being a well-rounded nursing professional. It uses friendly, accessible language to comprehensively cover all management theories & applies them to practical nursing settings.
The importance of leadership and management by nurses -- Understanding management and leadership -- How organisations shape leadership and management -- Understanding power, policy, and politics -- Leading and managing in teams -- Leading through communication -- Delegating successfully -- Motivating and developing others -- Working with conflict and difference -- Critical and creative thinking, decision-making, and problem-solving -- Leading and managing change and transition -- Self care : managing stress and time -- Budgeting, staffing, and managing resources -- Recruiting and selecting staff -- Clinical supervision, capability, and development review -- Quality improvement and risk management -- Information management.
U.K. adaptation of: Effective leadership and management in nursing / Eleanor J. Sullivan, Phillip J. Decker.
Keywords: Nursing services; Leadership; Nursing; Nursing, Supervisory; Leadership; Nurse Administrators; Nursing Care